ACD856, a novel positive allosteric modulator of Trk receptors, single ascending doses in healthy subjects: Safety and pharmacokinetics. - Nilsson, Boel; Bylund, Johan; Halldin, Magnus M.; Rother, Matthias; Rein-Hedin, Erik; Önnestam, Kristin; Segerdahl, Märta (European Journal of Clinical Pharmacology, 2024)
Purpose: AlzeCure Pharma AB is developing novel positive allosteric modulators of Trk-receptors for treatment of Alzheimer's disease, depression, other psychiatric conditions and other disorders where cognition is impaired. The preceding candidate drug ACD855 was shown to have a too long half-life in humans to allow further development. To de-risk the development of the follow-up compound ACD856, the oral single ascending dose study of ACD856 in humans was preceded by an intravenous microdose study, assessing the elimination half-life in plasma. Methods: A phase 0 study with a microdose of ACD856 (0.100 mg), was conducted in six healthy male subjects all receiving ACD856. Sequentially, a randomized, placebo-controlled, double-blind Phase I single ascending oral dose study (1 – 150 mg) was conducted, including 56 healthy subjects. Both studies assessed the safety and tolerability, as well as the PK properties of ACD856 after single dose intravenous and oral administration. Results: ACD856 was well tolerated with no treatment emergent, or dose related adverse events or other safety assessments. In the microdose study, ACD856 exhibited a bi-exponential plasma decline, low distribution volume, low plasma clearance with a half-life of approximately 20 hours. Orally, ACD856 exhibited rapid absorption, an almost complete bioavailability and a dose proportional increase in exposure. While the Cmax was lowered and delayed by food intake, the effect on plasma half-life and the overall bioavailability was low. No renal elimination of ACD856 was detected. Conclusion: The prediction proved accurate demonstrating the value of conducting a microdose study prior to ascending dose studies. Trial registration: NCT05783830 March 24, 2023 (microdose study, retrospectively registered) and NCT05077631 October 14, 2021 (single ascending dose study).